2023
DOI: 10.3390/microorganisms11082077
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathways and Functions of Indole-3-Acetic Acid in Microorganisms

Abstract: Indole-3-acetic acid (IAA) belongs to the family of auxin indole derivatives. IAA regulates almost all aspects of plant growth and development, and is one of the most important plant hormones. In microorganisms too, IAA plays an important role in growth, development, and even plant interaction. Therefore, mechanism studies on the biosynthesis and functions of IAA in microorganisms can promote the production and utilization of IAA in agriculture. This mini-review mainly summarizes the biosynthesis pathways that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Some IAA-producing bacterial strains isolated from alkali-salinated soils can increase the salt resistance of maize and wheat seeds during germination. In addition, it was shown that the production of IAA by bacteria contributed to the growth and salt resistance of perennial ryegrass, as well as upland cotton and pak choi plants [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some IAA-producing bacterial strains isolated from alkali-salinated soils can increase the salt resistance of maize and wheat seeds during germination. In addition, it was shown that the production of IAA by bacteria contributed to the growth and salt resistance of perennial ryegrass, as well as upland cotton and pak choi plants [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are five different pathways for the biosynthesis of IAA from tryptophan. Among them, the indole-3-acetamide pathway (IAM), the indole-3-pyruvic acid pathway (IPA/IPyA) and the tryptamine pathway (TAM) are the most common pathways in bacteria ( Zhang et al, 2019 ; Tang et al, 2023 ). The vital genes for the biosynthesis of tryptophan, including trpAB, trpC, trpD, trpEG, and trpF , were present in all 213 genomes of Stenotrophomonas .…”
Section: Resultsmentioning
confidence: 99%
“…Indole-3-acetic acid (IAA) is a signaling molecule that plays an important role in promoting plant growth (Tang et al 2023 ). Various pathways contribute to IAA production from tryptophan (Zhang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%